The Psychological Conflict of A Woman in Her Family as Seen in Jane Austen’s Persuasion - Raflis Raflis; Lekpi Panora (Jurnal Ilmiah Langue and Parole, 2023)
This research aims to describe the main character, the forms of psychological conflict get by the main character, and the main character efforts to resolve the psychological conflict in the novel Persuasion by Jane Austen. This research uses a literary psychology approach with Hippocrates character theory, Freud's personality, Freud's classification emotions, and Freud's ego defense mechanism. Method of collecting the data in this research is descriptive method. Method of analyzing the data in this research is a qualitative analysis method. Data collection technique of collecting the data in research obtained by library techniques, reading techniques, and notes-taking technique. The data analysis technique of analyzing data in this research is categorization step. The results of the research showed that the main character has a kind, patient, caring, act quickly and logistically, want to be love and love, pessimistic, and willing to sacrifice. The forms of psychological conflict that the main characters get are id, ego, superego, the concept of guilt, shame, hate, and love. The main character efforts to resolve psychological conflict get are regression, sublimation, estimation, repression, rationalization, reaction formation, and displacement.